The use of hormonal contraceptives by adolescents and possible health risks: An integrative review (Research, Society and Development, 2023)
The objective of the study was to analyze the health risks related to the use of hormonal contraceptives by the adolescent population in the literature. This is an integrative review of the literature, which included articles published and indexed in the databases National Library of Medicine (PUBMED), Medical Literature Analsis and Retrieval System On-line (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), Spanish Bibliographic Index of Health Sciences (IBECS), Nursing Database (BDENF), using the descriptors: “Adolescent”; “Hormonal Contraceptives” and “Risks to human health”, published between 2018 and 2023 in all languages. Therefore, 9 articles were included, which showed that the use of contraceptives in adolescents, despite being beneficial in some situations such as such as abortion, neonatality, it is essential to assess the risk arising from use in the adolescent population, especially with regard to mental health and risks of sexually transmitted infections. The findings of this review revealed some adverse effects, particularly mood changes. However, it suggests It is necessary that new research be carried out to investigate further adverse effects of the use of these contraceptives and real impacts on the general health of adolescents.